Challenges and Prospects in Enforcing Legal Protection of Children from Online Sexual Exploitation - Tourkia Rebhi; Ilyas Bouderbala (Krytyka Prawa, 2024)
The issue of online sexual exploitation of children is a growing concern worldwide, and there is a pressing need to strengthen legal protection measures for children. International laws and conventions have been established to protect children from online sexual exploitation, but the enforcement of these laws faces several challen ges, such as the difficulty of identifying perpetrators and the lack of resources and expertise in law enforcement agencies. Additionally, cultural and social norms may discourage children from reporting incidents of online sexual exploitation. However, there are prospects for improving legal protection measures, such as through increased international cooperation and coordination, awareness raising campaigns, and capacity building for law enforcement agencies. Overall, address ing the issue of online sexual exploitation of children requires a multifaceted approach involving legal, social, and technological measures